Aplikasi Pakan Kaya Karotenoid Hasil Fusi ProtoplasmIntergenera Dunaliella salina dan Chlorella vulgaris pada Udang Windu (Penaeus monodon F.) Stadia PL-20 Di Desa Asempapan, Pati, Jawa Tengah - Rahmawati, Novia; Zainuri, Muhammad; Kusumaningrum, Hermin Pancasakti (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2013)
Dunaliella salina and Chlorella vulgaris is a natural feed microalgae with high carotenoid content that can be increased using protoplast fusion technique. Protoplast fusion as one of the application fields of genetic engineering is a method for obtaining recombinant with the desired properties and profitable in a short time. This study aimed to see the effect of the addition of carotenoid-rich feed results from protoplast fusion recombinant D. salina and C. vulgaris on the survival rate and weight of shrimp post larvae. Mixed fusion results feed and artificial feed needed for the growth of post-larval shrimp, moulting and skin pigmentation. The results showed that the recombinant from protoplast fusion intergenera D. salina and C. vulgaris contains carotenoid pigments higher, reaching 124.6 mg / g bks from the second parent, namely D. salina reached 101.83 mg / g bks, while C. vulgaris 97.18 ug / g bks. Feed manufacturing is done by mixing pellets and 80-100x103 cells per 0.0225 g of feed. Application of feed carried on Penaeus monodon F. (tiger prawn) stadia PL-20 for a month. The results of weight measurements showed the highest prawn post larvae reached at artificial feeding plus recombinant protoplast fusion results intergenera D. salina and C. vulgaris and was able to raise the level of post-larval shrimp survival rate reached 88%. Â Keywords: D. salina, C. vulgaris, Protoplast Fusion, Carotenoid, Penaeus monodon F.